1977
DOI: 10.2134/agronj1977.00021962006900030001x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Conservation‐Tillage Environments on Growth and Productivity of Corn1

Abstract: Research on growth responses of corn (Zea mays L.) to environmental conditions associated with conservation‐tillage systems has not been extensively conducted. Therefore, the objectives of this study were to evaluate effects of various tillage systems (fall moldboard plow, till‐plant, no‐till ridge with and without previous‐crop residue) and early planting on growth and productivity of several corn genotypes (including two heterogeneous breeding populations that were improved for cold tolerance by recurrent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 7 publications
(7 reference statements)
11
79
1
Order By: Relevance
“…These results are consistent with the reports by Mock and Erbach ( 1977 ) , Hallauer and Colvin ( 1985 ), Anderson ( 1986), and Newhouse and Crosbie ( 1986), but contradict results of Brakke et al ( 1983 ) and Carter and Barnett ( 1987 ) . The study by Brakke et al ( 1983) was also conducted in the Central Plains, but tested the response of a very wide range of cultivars to cropping systems, combinations of tillage practice and water management (fallow or irrigation).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with the reports by Mock and Erbach ( 1977 ) , Hallauer and Colvin ( 1985 ), Anderson ( 1986), and Newhouse and Crosbie ( 1986), but contradict results of Brakke et al ( 1983 ) and Carter and Barnett ( 1987 ) . The study by Brakke et al ( 1983) was also conducted in the Central Plains, but tested the response of a very wide range of cultivars to cropping systems, combinations of tillage practice and water management (fallow or irrigation).…”
Section: Discussionsupporting
confidence: 92%
“…Conservation tillage systems are management strategies which reduce loss of soil and water relative to conventional tillage, through use of non-inversion tillage and retention of crop residues on the soil surface (Anonymous, 1982). Several studies have been conducted to define the response of maize to various tillage practices ( Alessi and Power, 197 1 ;Barber, 197 1;Mock and Erbach, 1977;Wilhelm et al, 1987). Generally, this research has indicated variability in the response of maize to tillage practice because of differences in soil temperature and water content.…”
Section: Introductionmentioning
confidence: 99%
“…Although soil temperature was not measured in this study, others have reported lower soil temperatures under mulches and in no-till conditions compared with bare soil and especially as it became drier (Adams et al 1970;Mock and Erbach 1977). Soils in Atlantic Canada are often saturated early in the growing season (Gartley et al1986).…”
Section: Corn Growth Parametersmentioning
confidence: 70%
“…Another result of residue or mulch cover in conservation tillage is an increase of soil moisture in the rooting profile (Burrows and Larsen, 1962;Barber, 1971;Blevins et aI., 1971;Bennet et aI., 1973;Griffith et aI., 1973;Mock and Erbach, 1977;Johnson and Lowery, 1985;Kladivko et aI., 1986;Lowery, 1986 andCarter and Barnett, 1987;Imholte and Carter, 1987;Cox et aI., 1990;Fortin, 1993). This is highly beneficial to production agriculture in areas where optimum rainfall does not always occur.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Colder temperatures tend to reduce growth and P and K diffusion to roots. Early growth of com is often reduced in no-till and mulch till in the Northern Com Belt compared with conventional tillage due to cooler soil temperatures (Griffith et aI., 1973;Mock and Erbach, 1977;AI-Darby and Lowery, 1986;Carter and Barnett, 1987;Imholte and Carter, 1987;Swan et aI., 1987;Kaspar et aI., 1990;Fortin and Pierce, 1991). Although delayed early growth and development under conservation tillage systems seldom reduces grain yield because corn often attains physiological maturity before a killing freeze in the fall (Swan et aI., 1987;Cox et aI., 1990).…”
Section: Literature Reviewmentioning
confidence: 99%